2022
DOI: 10.1002/brb3.2760
|View full text |Cite
|
Sign up to set email alerts
|

Association of increased pain intensity, daytime sleepiness, poor sleep quality, and quality of life with mobile phone overuse in patients with migraine: A multicenter, cross‐sectional comparative study

Abstract: Background : The number of regular smartphone users has increased dramatically worldwide. Headaches, followed by sleep difficulties, forgetfulness, dizziness, and other ailments, are among the most prevalent complaints among smartphone users during or after use. In addition, migraine is a debilitating disease and is the world's second leading cause of disability. Hence, we performed this study to determine how smartphone overuse influenced migraine patients' level of disability, pain intensity, slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…Surprisingly, participants with severe headaches tended to be low smartphone users, potentially indicating reduced smartphone usage among individuals dealing with more severe headache symptoms. A study from Pakistan reported an increase in pain intensity among high smartphone users with migraine headaches [11]. However, this difference may stem from our focus on different types of primary headaches.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Surprisingly, participants with severe headaches tended to be low smartphone users, potentially indicating reduced smartphone usage among individuals dealing with more severe headache symptoms. A study from Pakistan reported an increase in pain intensity among high smartphone users with migraine headaches [11]. However, this difference may stem from our focus on different types of primary headaches.…”
Section: Discussionmentioning
confidence: 90%
“…Numerous previous studies have explored the correlation between smartphone use and headaches, examining the severity and types of headaches and the utilization of medications. In an observational study conducted in Pakistan between 2021 and 2022 among patients with migraines categorized as high and low smartphone users, the results indicated that excessive smartphone use could exacerbate pain intensity and diminish the effectiveness of treatments for patients with migraines [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is also the second leading cause of disability worldwide caused by smartphone addiction. Examining the negative consequences of this technical breakthrough on its users is imperative 9 . Several issues have been attributed to the increasing internet usage, such as exposure to offensive images and content, invasions of privacy, and, in rare cases, addiction to the internet.…”
Section: Introductionmentioning
confidence: 99%